Analysis of Students Mathematical Problem-Solving Ability in Term of Multiple Intelligence - Dian Mayasari; Irmawaty Natsir; Abdul Rachman Taufik (Didaktik Matematika, 2021)
Many factors can influence students' ability to solve mathematical problems, and one of them is intelligence. The purpose of this study was to describe problem-solving abilities in terms of dominating multiple intelligences. The descriptive qualitative design was used for this investigation. The subjects of this study were six 7th-grade students chosen through purposive sampling based on dominating intellect in a group of six students. The data for this study were gathered through the use of validated questionnaires, interviews, and tests. The data analysis, which comprises data reduction, presentation, conclusion. Findings of this study show that pupils with naturalist, interpersonal, kinesthetic intelligence are able to solve problems according to plan, and loocking back when they are incorrect. Students with dominating intelligences such as linguistic-verbal, logical-mathematical, and visual-spatial can plan, conduct step-by-step rechecking of the solution to a problem that has not yet been finished. Furthemore, the effect of various intelligences can solve mathematics problems successfully.